KORELASI KEPADATAN LALU LINTAS DENGAN KADAR SULFUR DIOKSIDA (SO2) DAN KLOROFIL THALLUS LICHEN SEBAGAI BIOINDIKATOR PADA TEGAKAN POHON ANGSANA (Pterocarpus Indicus Willd.) DI KAWASAN INDUSTRI MEDAN II - Pohan, Muslimah; Hasairin, Ashar (Biospecies, 2025)
Air pollution is an unresolved environmental problem to date. Traffic density will have a direct impact on the increase of various types of exhaust emissions, one of which is sulfur dioxide (SO2). Efforts that can be made to prevent further air pollution is to monitor air quality with biomonitoring utilizing lichen as a bioindicator. This study aims to identify the type of lichen species used as bioindicators in Angsana (Pterocarpus indicus Willd.) tree stands, to analyze the correlation of traffic density with sulfur dioxide (SO2) levels in lichen thallus, to analyze the correlation of traffic density with chlorophyll levels in lichen thallus, and to analyze the correlation of sulfur dioxide (SO2) levels with chlorophyll levels in lichen thallus in Medan Industrial Area II. This research is descriptive quantitative with road sampling method on Angsana tree stands in the research location. The results showed that Lichen Lepraria incana and Drinaria picta were obtained as bioindicators in both research locations. The correlation of traffic density with sulfur dioxide levels in lichen thallus showed a very strong positive correlation between traffic density and SO₂ levels with a Pearson correlation value of 0.985 and a significance value (p-value) of 0.015. Since the p-value < 0.05, this relationship is statistically significant. The correlation of traffic density with chlorophyll levels in lichen thallus showed a strong negative correlation and was also statistically significant (p-value < 0.05) with a Pearson Correlation value of -0.958 with a significance value of 0.042. Correlation of sulfur dioxide (SO2) levels with chlorophyll levels in lichen thallus showed a strong negative correlation, but not statistically significant because the p-value> 0.05 with a Pearson Correlation value of -0.943 with a p-value of 0.057.